Hydrogel‐Enabled Transfer‐Printing of Conducting Polymer Films for Soft Organic Bioelectronics. (22nd November 2019) - Zhang, Shiming; Ling, Haonan; Chen, Yihang; Cui, Qingyu; Ni, Jiahua; Wang, Xiaochen; Hartel, Martin C.; Meng, Xiang; Lee, KangJu; Lee, Junmin; Sun, Wujin; Lin, Haisong; et al.
Abstract: The use of conducting polymers such as poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) for the development of soft organic bioelectronic devices, such as organic electrochemical transistors (OECTs), is rapidly increasing. However, directly manipulating conducting polymer thin films on soft substrates remains challenging, which hinders the development of conformable organic bioelectronic devices. A facile transfer‐printing of conducting polymer thin films from conventional rigid substrates to flexible substrates offers an alternative solution. In this work, it is reported that PEDOT:PSS thin films on glass substrates, once mixed with surfactants, can be delaminated with hydrogels and thereafter be transferred to soft substrates without any further treatments. The proposed method allows easy, fast, and reliable transferring of patterned PEDOT:PSS thin films from glass substrates onto various soft substrates, facilitating their application in soft organic bioelectronics. By taking advantage of this method, skin‐attachable tattoo‐OECTs are demonstrated, relevant for conformable, imperceptible, and wearable organic biosensing. Abstract : The use of hydrogels enables transfer‐printing of poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate thin films from glass substrates onto various soft substrates. Taking advantage of this technique, skin‐attachable organic electrochemical transistors (OECTs) are fabricated on commercially available tattoo paper. Wearable tattoo‐OECTs are further demonstrated with the integration of a wireless readout system.